2021
DOI: 10.3390/bs11050074
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Parkinson’s Disease: Epidemiology, Clinical Profile, Protective and Risk Factors

Abstract: Cognitive impairment is a common non-motor symptom in Parkinson’s Disease (PD) and an important source of patient disability and caregiver burden. The timing, profile and rate of cognitive decline varies widely among individuals with PD and can range from normal cognition to mild cognitive impairment (PD-MCI) and dementia (PDD). Beta-amyloid and tau brain accumulation, oxidative stress and neuroinflammation are reported risk factors for cognitive impairment. Traumatic brain injury and pesticide and tobacco exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 182 publications
(213 reference statements)
2
24
0
Order By: Relevance
“…Of note, the study reported that 80% of PD patients were complicated with cognitive impairment, and 30% of patients developed Parkinson's dementia. Some studies have found that the occurrence of dementia in patients with PD is not only related to cognitive impairment but also related to serum inflammatory factors [ 30 ]. Serum MIF is a marker of slow and acute inflammation, which can promote the development of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the study reported that 80% of PD patients were complicated with cognitive impairment, and 30% of patients developed Parkinson's dementia. Some studies have found that the occurrence of dementia in patients with PD is not only related to cognitive impairment but also related to serum inflammatory factors [ 30 ]. Serum MIF is a marker of slow and acute inflammation, which can promote the development of PD.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been little systematic effort to determine whether Pink1-/-rats also model PD-relevant cognitive or memory phenotypes. This is despite evidence that among genetically determined forms of PD, patients with Pink1 mutations have the greatest incidence of cognitive dysfunction and decline (Piredda, Desmarais et al 2020, Gonzalez-Latapi, Bayram et al 2021). To fill this gap in knowledge, longitudinal testing using Novel Object Recognition (NOR), Novel Object Location (NOL) and Object in Place (OiP) paradigms was used to determine whether and when Pink1 -/-rats express deficits similar to the impairments in visual recognition memory and//or visuospatial information processing that commonly occur in PD patients (Owen, Beksinska et al 1993, Higginson, Wheelock et al 2005, Possin, Filoteo et al 2008, Fang, Lv et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease is characterized by a gradual loss and degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc). Its etiology is associated with several risk factors (environmental factors) and family history) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%